Global Foot‐and‐Mouth Disease Research Update and Gap Analysis: 6 – Immunology. (June 2016) - Robinson, L.; Knight‐Jones, T. J. D.; Charleston, B.; Rodriguez, L. L.; Gay, C. G.; Sumption, K. J.; Vosloo, W.
Summary: This study assessed gaps and priorities for FMDV (foot‐and‐mouth disease virus) research in the field of immunology. The study took the form of a literature review (2011‐15) combined with research updates collected in 2014 from 33 institutes from across the world. Findings were used to identify priority areas for future FMD research. Improved understanding of FMDV immunology facilitates the development of vaccines, adjuvants and diagnostic tests, and will allow better assessment and prediction of vaccine potency and match, with reduced use of animals, particularly large animals, in experimental studies. Continued characterization of the immune systems of several FMD host species has underpinned substantial advances in knowledge of their interaction with FMDV. Recent studies have shed light on the mechanisms underlying formation of the bovine B‐ and T‐cell response; there is also a greater understanding of the significance of non‐neutralizing antibodies during FMDV infection and the interactions of antibody‐bound virus with immune cells. This knowledge is directly relevant to vaccine development, as well as understanding protection and cross‐protection. Despite ongoing research, significant knowledge gaps remain in the areas of neonatal and mucosal immunity. The impact of maternally derived antibody upon the neonate's ability to respond to FMD vaccination has received some attention, but few firm conclusions can be drawn at this stage, and little is known of the cellular response of young animals in general. The mucosal immune system of FMDV‐susceptible species requires continued characterization, especially if the potential of mucosal vaccine‐delivery systems is to be realized for FMD immunization.